Rekayasa Kualitas Kompos Brangkasan Kacang Tanah Dan Jerami Padi Terhadap Pertumbuhan Dan Produksi Tanaman Padi Gogo (Oryza Sativa L.) - Anton Cahyo Prabowo; Anis Sholihah; Siti Muslikah (AGRONISMA, 2019)
This study aims to determine the effect of adding peanut stover compost and straw in various compositions to the growth and yield of upland rice. The study was conducted in February to June 2018 in the plastic house of Losari Village, Singosari District, Malang Regency. The composting process was carried out at the Composite Laboratory of the Faculty of Agriculture, Islamic University of Malang. The results showed the growth of average upland rice on 100% peanut stover compost (plant length of 104.10 cm, number of tillers 37.33 tillers and leaf area of 9010.02 cm2) and the best production of K3 treatment (50% stover soil + 50% rice straw) with grain weight of 6.19 tons ha-1.